Balancing and compensating extractions in primary teeth: How age, gender, and clinical setting shape pediatric dentists’ preferences - Eser Rengin Nalbantoglu; Parmjit Singh (Journal of Indian Society of Pedodontics and Preventive Dentistry)
Context: Balancing and compensating extractions (BCEs) of primary teeth are widely practiced in pediatric dentistry to prevent space loss and midline deviations. However, pediatric dentists’ preferences regarding BCEs may be influenced by various demographic and professional factors. Understanding these preferences is essential for standardizing guidelines and optimizing clinical decision-making. Aims: This study aims to investigate whether pediatric dentists’ preferences for BCEs of primary teeth within the British Society of Paediatric Dentistry (BSPD) are influenced by age, gender, clinical work setting, and referral practices to orthodontists. Settings and Design: A survey of the total population of BSPD members was conducted to explore variations in BCE practices based on demographic and professional characteristics. Subjects and Methods: A structured online survey was distributed to 288 BSPD members. The questionnaire included demographic questions and clinical case scenarios related to BCEs. The survey was pilot-tested and validated before distribution. The study adhered to national clinical guidelines, and ethical approvals were obtained. Statistical Analysis Used: Categorical data were analyzed using descriptive statistics. Contingency tables were generated to compare groups, and statistical significance was assessed using Chi-square or Fisher’s exact tests, where appropriate. Cramér’s V (CV) test was used to determine effect sizes. Statistical significance was set at P < 0.05. Results: Over 80% of pediatric dentists adhered to national guidelines for BCEs, with secondary care practitioners exhibiting a slightly higher adherence rate (86%) compared to primary care practitioners (66.7%). Significant differences in BCE practices were found for primary canines in crowded arches by clinical setting (P = 0.001, CV = 0.493), for first molars in crowded arches by gender (P = 0.05, CV = 0.319), and for primary canines in spaced arches by age (P = 0.001, CV = 0.463). For children aged 6–9 years, differences were significant for primary canines in crowded arches by clinical settings (P = 0.004, CV = 0.436) and for first molars in spaced arches by gender (P = 0.034, CV = 0.376). Older pediatric dentists (over 50 years) were significantly less likely to refer patients for orthodontic opinions than younger dentists (P = 0.019, CV = 0.317). Conclusions: Pediatric dentists’ BCE preferences are influenced by their clinical work settings, age, and gender. The study highlights the need for standardizing BCE guidelines and emphasizes the importance of interdisciplinary collaboration with orthodontists to ensure evidence-based, uniform decision-making.